E-lerning concept design of rijndael encryption process - Zainuddin, Zahir; Manullang, Evanita V. (2013 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE), 2013)
In the subject of Computer Security, there is a learning topic about cryptography. Numbers of meeting for the subject do not enable students to learn the cryptography algorithm that make the students do not fully understand about the working way of some cryptography algorithms. There are many cryptography algorithms. However, only rijndael encryption algorithm will be described in this writing. Rijndael algorithm is chosen because it is considered difficult to solve. The reason is because its process is also difficult to perform. Generally, not all students can understand the encryption process by only reading books. Therefore, it is clear that an application which provides rijndael algorithm learning concept by presenting the input is needed, so the students can clearly get the point in every process occurred in that algorithm.